A Progressive Review of V600E-B-RAF-Dependent Melanoma and Drugs Inhibiting It - Khan, Mohammad Ashrafuddin; El-Gamal, Mohammed I.; Oh, Chang-Hyun (BENTHAM SCIENCE PUBL LTD, 2017)
B-RAF gene is a component of the MAPK pathway that plays a very important role in cell division, survival, proliferation, and many other cellular functions. Mutations of the B-RAF (such as V600E-B-RAF) lead to melanoma, which is one of the leading causes of death worldwide. R&D progress is being done aiming at improved therapy in the future. The existing melanoma therapy is left out with poor overall survival, drug resistance, and many side effects. With the recent approval of new drugs, there is a hope for melanoma patients for complete cure and better life quality. However, there is still a need for improved, safe, and complete therapy for advanced melanoma. This review describes melanoma caused by V600E-B-RAF gene mutation, its pathway, drugs available and recently approved drugs, and future prospects to be overcome.
Keywords: CYCLIN D1 EXPRESSION; METASTATIC MELANOMA; BRAF MUTATIONS; BRAF(V600E) INHIBITION; PTEN/MMAC1 ALTERATIONS; DABRAFENIB GSK2118436; COMBINATION THERAPY; ACQUIRED-RESISTANCE; MALIGNANT-MELANOMA; SIGNALING PATHWAY